Upaya Meningkatkan Pengetahuan Konservasi Sumberdaya Hayati Ikan Endemik Depik di Danau Laut Tawar Melalui Kegiatan Outing Class SDIT Sunnah An-Najah Aceh Tengah - Syaiful Ramadhan Harahap; Martin Heryan; Ahmad Nafiah; Anna Fitriana; Aris Hidayatullah; Gunadi Setia (PELANTAR PRESS, 2023)
The survival of the endemic depik fish in Lake Laut Tawar is threatened by the over-utilization of fish biological resources and the decline in environmental quality. This situation is believed to result from the community's lack of knowledge and understanding of endemic fish and their life aspects. To address this issue, sustainable efforts are required to conserve the biological resources of the depik fish, one of which involves enhancing public knowledge and understanding through counselling sessions. As part of a community service activity, counselling occurred on December 1, 2022, coinciding with an outing class of students from SDIT Sunnah An-Najah in Takengon, Central Aceh. The activity consisted of three sessions: 1) administering an initial questionnaire (pre-test) to assess baseline knowledge, 2) delivering informative material through counselling, and 3) evaluating the achievements of the activity. The overall evaluation results indicated that the partners' average knowledge increased by 51.19% after the counselling session. To ensure the continuity and consistency of depik fish's biological resource conservation in Lake Laut Tawar, it is recommended to incorporate learning about fish biological resource conservation into the curriculum and local school content.